Experience-dependent information routing through the basolateral amygdala shapes behavioral outcomes - Antonoudiou, Pantelis; Stone, Bradly T.; Colmers, Phillip L.W.; Evans-Strong, Aidan; Teboul, Eric; Walton, Najah L.; Weiss, Grant L.; Maguire, Jamie (Cell reports (Cambridge), 2024)
It is well established that the basolateral amygdala (BLA) is an emotional processing hub that governs a diverse repertoire of behaviors. Selective engagement of a heterogeneous cell population in the BLA is thought to contribute to this flexibility in behavioral outcomes. However, whether this process is impacted by previous experiences that influence emotional processing remains unclear. Here we demonstrate that previous positive (enriched environment [EE]) or negative (chronic unpredictable stress [CUS]) experiences differentially influence the activity of populations of BLA principal neurons projecting to either the nucleus accumbens core or bed nucleus of the stria terminalis. Chemogenetic manipulation of these projection-specific neurons can mimic or occlude the effects of CUS and EE on behavioral outcomes to bidirectionally control avoidance behaviors and stress-induced helplessness. These data demonstrate that previous experiences influence the responsiveness of projection-specific BLA principal neurons, biasing information routing through the BLA, to drive divergent behavioral outcomes. [Display omitted] •Previous experiences alter electrophysiological properties of principal neurons in the BLA•Previous experiences differentially alter the activity of projection-specific BLA neurons•Chemogenetic biasing of information flow through the BLA bidirectionally impacts behavior•Previous experiences bias information routing through the BLA to drive divergent behaviors Antonoudiou et al. demonstrate that previous experiences, both positive and negative, influence information routing through the BLA to produce divergent behaviors. They demonstrate that CUS or EE exposure differentially impact the activity of projection-specific BLA neurons and that manipulating these unique circuits can bidirectionally control behavioral outcomes.